Utilisation Of Clamshells As Aggregate Substitute In Paving Blocks - Maulana, Arman; Sulfanita, Andi; Widarto, Hendro; Adnan, Adnan (Journal of Renewable Engineering, 2024)
Paving blocks are becoming more popular among consumers because they are environmentally friendly, can save groundwater, are easy to install and maintain, and have many shapes that add aesthetic value. This study aims to determine the difference of shells on the water absorption capacity of paving blocks and the strength of paving blocks. Experiments were conducted at the structure and materials laboratory of Muhammadiyah University of Parepare from August to October 2023 for this research method. The results showed that the water absorption of paving blocks was influenced by the addition of seashells. The water absorption values of the 0%, 5%, 10%, and 25% variations were 1.4 percent, 2 percent, 3.4 percent, and 3.7 percent for the 7-day treatment period; 0.6 percent, 1.7 percent, 2.4 percent, and 3.3 percent for the 14-day treatment period; and 1.3%, 2.8 percent, 3.0 percent, and 4.6 percent for the 28- day treatment period. According to the above results, the more clamshells added, the greater the water absorption. The compressive strength shows that the addition of clamshells affects the compressive strength of block paving. The compressive strength values were 23.841 Mpa, 9.365 Mpa, 21.587 Mpa, and 11.429 Mpa at the 28-day curing age, respectively. The more clamshells added, the lower the compressive strength.